1991
DOI: 10.1111/j.1530-0277.1991.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Ro15‐4513 Attenuates the Consumption of Ethanol in Deprived Rats

Abstract: This research investigated the effects of Ro15-4513 (Ro15), a partial inverse benzodiazepine agonist, on the drinking behavior of 23-1/2 hr fluid deprived rats. Water-deprived rats were maintained on a two-bottle regimen of a saccharin-ETOH solution along with tap water available for 30 min/day for several days. Following this acclimation period, animals were pretreated with either Ro15 (1.0, 2.5, and 5.0 mg/kg) or Tween-80 vehicle injections. Pretreatment with Ro15 at all doses tested resulted in a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These effects include increased exploration and locomotion at very low doses (0.25, 0.5, and 0.75 g͞kg in rats) (61), the anxiolytic effects at low doses (1 g͞kg) (17,39), and sedative, motor-impairing as well as the amnestic effects at moderate alcohol doses (2 g͞kg) (17,19,21,62). In addition, the observation that Ro15-4513 reduces alcohol self-administration (23,24,63) suggests that the rewarding effects of ethanol might be mediated by ethanol͞Ro15-4513-sensitive GABA A Rs. However, Ro15-4513 does not prevent all ethanol effects: at higher alcohol doses (Ն2 g͞kg in rats), Ro15-4513 significantly reduces, but does not prevent the anesthetic (''sleep''-inducing) effects of ethanol, and Ro15-4513 does not prevent the hypothermic effects of ethanol (32,64).…”
Section: Discussion Extrasynaptic ␦ Subunit-containing Receptors As Tmentioning
confidence: 99%
“…These effects include increased exploration and locomotion at very low doses (0.25, 0.5, and 0.75 g͞kg in rats) (61), the anxiolytic effects at low doses (1 g͞kg) (17,39), and sedative, motor-impairing as well as the amnestic effects at moderate alcohol doses (2 g͞kg) (17,19,21,62). In addition, the observation that Ro15-4513 reduces alcohol self-administration (23,24,63) suggests that the rewarding effects of ethanol might be mediated by ethanol͞Ro15-4513-sensitive GABA A Rs. However, Ro15-4513 does not prevent all ethanol effects: at higher alcohol doses (Ն2 g͞kg in rats), Ro15-4513 significantly reduces, but does not prevent the anesthetic (''sleep''-inducing) effects of ethanol, and Ro15-4513 does not prevent the hypothermic effects of ethanol (32,64).…”
Section: Discussion Extrasynaptic ␦ Subunit-containing Receptors As Tmentioning
confidence: 99%
“…Hyytiä and Koob (1995) reported a decrease in ethanol self-administration following GABA A receptor antagonism in the basal forebrain. Similarly, ligands at the benzodiazepine binding site of the GABA A receptor predictably a¤ect ethanol consumption, agonists modestly increasing ethanol intake (Wegelius et al 1994) and inverse agonists strongly suppressing it (Samson et al 1987;Balakleevsky et al 1990;June et al 1991;Rassnick et al 1993;Wegelius et al 1994). In this context, it is interesting to note that there are di¤erences in the pharmacology of brain GABA A receptors between alcohol-preferring and alcohol-avoiding rat lines (Wong et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These publications all reported significant reductions in ethanol intake by male and female, adolescent and adult P rats using both home-cage and operant procedures. Peripheral testing with the pan-opioid antagonists, naloxone (Badia-Elder et al, 1999; June et al, 1991) and nalmefene (June, Grey, et al, 1998), also revealed significant reductions in ethanol intake by male and female, adolescent and adult P rats using both home-cage and operant procedures. Another study reported that nalmefene microinjections into the NAcb, Hipp and VTA significantly reduced operant alcohol self-administration by adult female P rats (June et al, 2004).…”
Section: Some Neurochemical Neuropharmacological As Well As Neurmentioning
confidence: 99%